2022
DOI: 10.7759/cureus.26245
|View full text |Cite
|
Sign up to set email alerts
|

Novice Doctors in the Emergency Department: A Scoping Review

Abstract: In many emergency departments (EDs), young, inexperienced doctors treat patients who are critically ill. At the start of their career, these novice doctors are not sufficiently qualified to take care of these potentially critically ill patients in the highly demanding environment of an ED. This not only poses a threat to the wellbeing of the doctor, who feels inadequately prepared and experiences a lot of stress, but also to that of the patients, who may not receive optimal care. Lastly, young doctors may infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Sakuma et al reported that resident trainee dentists experienced more incidents of a higher level of severity than did staff dentists in Japan [18]. Almost half of the participants who were intern doctors had been assigned to tasks for which they were not trained or for which medical errors could have happened easily [19]. Medical interns are not only factors in the liveware category, which included missed treatment procedures or missed judgements, but also the environmental category, which included the lack of experienced staff and instructors.…”
Section: Dental Interns Were More Likely To Report Incidents Than Wer...mentioning
confidence: 99%
“…Sakuma et al reported that resident trainee dentists experienced more incidents of a higher level of severity than did staff dentists in Japan [18]. Almost half of the participants who were intern doctors had been assigned to tasks for which they were not trained or for which medical errors could have happened easily [19]. Medical interns are not only factors in the liveware category, which included missed treatment procedures or missed judgements, but also the environmental category, which included the lack of experienced staff and instructors.…”
Section: Dental Interns Were More Likely To Report Incidents Than Wer...mentioning
confidence: 99%